Design method and preparation method of TiZrNbSn alloy with ultralow elastic modulus and high superelasticity

By adjusting the composition of Zr, Nb and Sn in titanium alloys, an ultra-low elastic modulus and super-elastic TiZrNbSn alloy was designed, which solved the problems of high elastic modulus and low ultra-elastic recovery strain in the biomedical field of existing titanium alloys, and achieved better mechanical matching and biocompatibility.

CN119710430APending Publication Date: 2025-03-28XIAN UNIV OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411787773.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the field of biomedical medicine, the implants do not match the mechanics of human tissue due to the high elastic modulus, resulting in stress concentration and damage, and the superelastic recovery strain is small, making it difficult to meet the needs of biomedical applications.

Method used

A super elastic TiZrNbSn alloy is designed to adjust the composition of Zr, Nb and Sn, and reduce the elastic modulus of the alloy and the martensite reverse phase transformation point, thereby promoting the generation of texture, thereby improving the super elastic recovery strain.

Benefits of technology

The ultra-low elastic modulus and high super elastic properties of the alloy are achieved, which enhances the mechanical matching between the implant and human tissues, reduces stress concentration and damage, and improves biocompatibility and tissue regeneration environment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710430A_ABST
    Figure CN119710430A_ABST
Patent Text Reader

Abstract

The invention discloses a design method and a preparation method of a TiZrNbSn alloy with ultralow elastic modulus and high superelastic.Zr and Nb components in the alloy are designed according to a Ti-Zr binary phase diagram and a critical electron / atomic ratio function of a Ti-M alloy, meanwhile, the Sn content is designed according to the influence of all elements on Af, and the TiZrNbSn alloy comprises, by atomic percent, 34.5%-35.5% of Zr, 8.7%-9.3% of Nb, 1.4%-1.6% of Sn and the balance Ti. The balance is Ti and inevitable impurities; after the TiZrNbSn alloy is subjected to homogenization treatment, cold rolling and solution treatment, the elastic modulus is as low as 41.34 GPa, and the total recovery strain epsilon r and the superelastic recovery strain epsilon se respectively reach 4.28% and 3.16%, so that the prepared TiZrNbSn alloy has competitive advantages in medical metal implant materials and orthodontic materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of alloy materials, and in particular relates to a design method and a preparation method of an ultra-low elastic modulus and high superelastic TiZrNbSn alloy. Technical Background

[0002] With the continuous development of medical technology and the increase in people's demand for health, the requirements for medical metal materials are also increasing. Titanium and titanium alloys, as a class of excellent metal materials, have excellent mechanical properties, biocompatibility and corrosion resistance. Their unique physical and chemical properties make them one of the most promising medical metal materials.

[0003] Pure titanium and Ti6Al4V alloys, which are widely used in the biomedical field, have an elastic modulus of 110 to 120 GPa, which is much higher than the elastic modulus of human bones (10 to 30 GPa). Implants with high elastic modulus are prone to the "stress shielding" effect, causing the tissue around the implant to degenerate, and then causing the implant to loosen and fail. Implants with low elastic modulus can match the mechanical properties of biological tissues, increase the adaptability of implants, reduce stress concentration and damage caused by mechanical mismatch, usually have better biocompatibility, and can also reduce inflammatory reactions and fibrosis, help integrate materials with surrounding tissues, reduce negative effects on surrounding tissues, and provide an environment more conducive to cell growth and angiogenesis, thereby promoting tissue regeneration.

[0004] On the other hand, during the development of titanium alloys, researchers found that some titanium alloys produce reversible martensitic phase transformation during deformation and show a certain degree of superelasticity. Superelastic implants have the advantages of reducing fit, promoting bone growth and protecting brittle bones, which further broadens the application of titanium alloys in the biomedical field. In biomedical applications, superelasticity that occurs near human body temperature is essential for orthodontic wires, stents and bone implants. At present, a variety of non-toxic titanium alloys with superelasticity at room temperature have been developed, but the total elastic recovery strain is still small, and the maximum recoverable strain of most titanium alloys is only 2%. Therefore, how to further reduce the elastic modulus of titanium alloys and improve superelasticity is an urgent problem to be solved. Summary of the invention

[0005] In order to solve the above technical problems, the object of the present invention is to provide a design method and a preparation method of an ultra-low elastic modulus and high superelastic TiZrNbSn alloy.

[0006] The technical solution adopted by the present invention is:

[0007] A design method of an ultra-low elastic modulus high superelastic TiZrNbSn alloy specifically comprises the following steps:

[0008] Step 1, designing the composition of the Zr element. The elastic modulus of the alloy is determined by the bonding force between atoms in the alloy. The weaker the bonding force, the lower the elastic modulus. The atomic bonding force is estimated according to the melting temperature in the Ti-Zr alloy binary phase diagram. When the Zr content is 35 at.%, it corresponds to the lowest melting temperature. At this time, the bonding force between atoms is the lowest and the elastic modulus is the lowest. The Zr content is designed to be 34.5-35.5 at.%;

[0009] Step 2, designing the composition of the Nb element. According to the critical electron / atom ratio function of the Ti-M alloy, when the valence electron concentration is 4.09, the elastic modulus is the lowest, and a metastable β-titanium structure can be obtained. In the TiZrNbSn alloy, e / a=4+(5-4)*(Nb at.%), and the Nb content is designed to be 8.7-9.3 at.%.

[0010] Step 3, design the composition of Sn element, and adjust the martensitic transformation end temperature A according to different alloy elements. f The impact of A f [℃] = 1165-75·Nb[at%]-10·Zr[at%]-100·Sn[at%], designing the A of TiZrNbSn alloy f At around room temperature, the Sn content is designed to be 1.4 to 1.6 at.%.

[0011] The invention discloses a TiZrNbSn alloy with ultra-low elastic modulus and high superelasticity, which comprises Ti, Zr, Nb and Sn elements. The composition of the TiZrNbSn alloy comprises 34.5-35.5% of Zr, 8.7-9.3% of Nb, 1.4-1.6% of Sn by atomic percentage, and the balance is Ti and unavoidable impurities. The purity of the raw materials is 99.99%.

[0012] A method for preparing an ultra-low elastic modulus high superelastic TiZrNbSn alloy specifically comprises the following steps:

[0013] Step 1, Ti, 34.5-35.5% Zr, 8.7-9.3% Nb, and 1.4-1.6% Sn raw materials are loaded into a crucible of a vacuum argon arc melting furnace in proportion, the furnace chamber is evacuated and filled with inert gas as a protective gas, an ingot is obtained after melting once, and then the ingot is turned over and melted multiple times to obtain a TiZrNbSn alloy ingot;

[0014] Step 2, performing homogenization heat treatment on the TiZrNbSn alloy ingot obtained in step 1, and then water cooling to room temperature;

[0015] Step 3, cold rolling the TiZrNbSn alloy ingot processed in step 2 to obtain an alloy plate;

[0016] Step 4: performing a solution heat treatment on the alloy plate obtained in step 3 to obtain a β-phase TiZrNbSn alloy.

[0017] Furthermore, the pressure of the furnace chamber after vacuuming in step 1 is less than 5×10 -3 Pa, smelting is carried out under the protection of inert gas argon, the current of the smelting process is 400-600A, and the electromagnetic stirring current is 5-10A. After stopping the smelting, the raw materials are quickly solidified into ingots under the action of circulating cooling water at the bottom of the crucible, and then the ingots are turned over and re-smelted to obtain TiZrNbSn alloy ingots with uniform composition.

[0018] Furthermore, the smelting in step 1 is performed 6 times or more.

[0019] Furthermore, the homogenization heat treatment in step 2 is carried out at a vacuum degree of less than 5×10 -3 Pa, heat treatment at 1000℃ for 2h.

[0020] Furthermore, the cold rolling process in step 3 is a multi-pass rolling in the same direction at room temperature.

[0021] Furthermore, in step 3, the cold rolling deformation is greater than 90%.

[0022] Furthermore, the solution heat treatment in step 4 is performed at 900° C. for 0.5 h under argon protection, and then water-cooled to room temperature.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The TiZrNbSn alloy provided by the present invention is designed based on the melting temperature and valence electron theory affected by the atomic bonding force. The atomic bonding force is estimated based on the melting temperature in the Ti-Zr alloy binary phase diagram. The Zr content corresponds to the lowest melting temperature when it is 35at.%, at which time the interatomic bonding force is the lowest and the elastic modulus is the lowest. According to the critical electron / atom ratio (e / a) function of the Ti-M alloy, the elastic modulus is the lowest when the valence electron concentration (e / a) is 4.09, and a metastable β-titanium structure can be obtained. In addition, by analyzing and summarizing the effects of different alloying elements on the martensitic reverse transformation end temperature (A f ) is affected by the design of the alloy A fAt room temperature, stress-induced martensitic transformation occurs under external stress and can mostly rebound, producing obvious superelasticity. The alloy increases the Zr content and increases the β-phase lattice distortion to ensure that the martensitic transformation process produces a large phase transformation strain. The alloy adds appropriate amounts of Nb and Sn elements, which, on the one hand, reduce the reverse phase transformation point and elastic modulus of martensitic transformation, and on the other hand, promote <011> The generation of texture, along <011> Tensile deformation is conducive to martensitic transformation and to obtaining higher superelasticity. Therefore, in the process of alloy design, ~35at.% Zr is added to obtain low elastic modulus and increase β phase lattice distortion; ~9at.% Nb is added to stabilize the β phase while reducing the elastic modulus and promoting Zr and Sn to reduce the martensitic reverse phase transformation point; ~1.5at.% Sn is added to ensure that the martensitic reverse phase transformation point drops to near room temperature and promote <011> The creation of texture.

[0025] The preparation method of the TiZrNbSn alloy of the present invention can realize the control of the alloy grain size and texture by controlling the process parameters, and can obtain an average grain size of 150 μm to 200 μm. <011> The TiZrNbSn alloy has a texture content exceeding 85%. The TiZrNbSn alloy exhibits ultra-low elastic modulus and high superelasticity in tensile deformation. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a grain orientation distribution diagram of the TiZrNbSn alloy along the rolling direction obtained by the design method and preparation method of an ultra-low elastic modulus and high superelastic TiZrNbSn alloy in Example 1 of the present invention.

[0027] Figure 2 The TiZrNbSn alloy obtained by the design method and preparation method of an ultra-low elastic modulus and high superelastic TiZrNbSn alloy in the rolling direction is <110> Oriented grain distribution and proportion diagram.

[0028] Figure 3 This is a cyclic tensile stress-strain curve of a TiZrNbSn alloy obtained by a design method and a preparation method of an ultra-low elastic modulus and high superelastic TiZrNbSn alloy according to Example 1 of the present invention.

[0029] Figure 4 This is a conventional tensile stress-strain curve of a TiZrNbSn alloy obtained by a design method and a preparation method of an ultra-low elastic modulus and high superelastic TiZrNbSn alloy according to Example 1 of the present invention. DETAILED DESCRIPTION

[0030] The following is a detailed description through specific embodiments in conjunction with the accompanying drawings.

[0031] A design method of an ultra-low elastic modulus high superelastic TiZrNbSn alloy specifically comprises the following steps:

[0032] Step 1, design the composition of the Zr element. The elastic modulus of the alloy is determined by the bonding force between atoms in the alloy. The weaker the bonding force, the lower the elastic modulus. The atomic bonding force can be estimated based on the melting temperature in the Ti-Zr alloy binary phase diagram. The Zr content corresponds to the lowest melting temperature when it is 35 at.%, at which time the atomic bonding force is the lowest and the elastic modulus is the lowest. Taking into account the experimental error, the Zr content is designed to be 34.5-35.5 at.%.

[0033] Step 2, design the composition of the Nb element. According to the critical electron / atom ratio (e / a) function of the Ti-M alloy, when the valence electron concentration (e / a) is 4.09, the elastic modulus is the lowest, and a metastable β-titanium structure can be obtained. In the TiZrNbSn alloy, e / a=4+(5-4)*(Nb at.%). Considering the experimental error, the Nb content is designed to be 8.7-9.3 at.%.

[0034] Step 3, design the composition of Sn element. By analyzing and summarizing the effects of different alloying elements on the martensitic reverse transformation end temperature (A f ) f [℃] = 1165-75·Nb[at%]-10·Zr[at%]-100·Sn[at%]), designing the A of TiZrNbSn alloy f At room temperature, the Sn content is designed to be 1.4 to 1.6 at. %, taking into account experimental errors.

[0035] An ultra-low elastic modulus and high superelastic TiZrNbSn alloy comprises Ti, Zr, Nb and Sn elements, and in terms of atomic percentage, comprises 34.5-35.5% Zr, 8.7-9.3% Nb, 1.4-1.6% Sn, and the remainder is Ti and unavoidable impurities. The raw materials involved in the alloy smelting include: Ti, Nb, Zr, and Sn, and the purity of the raw materials is 99.99%.

[0036] A method for preparing an ultra-low elastic modulus high superelastic TiZrNbSn alloy specifically comprises the following steps:

[0037] Step 1: 34.5-35.5% Zr, 8.7-9.3% Nb, and 1.4-1.6% Sn raw materials are loaded into a crucible of a vacuum argon arc melting furnace in proportion, the furnace chamber is evacuated and filled with argon as a protective gas, and the vacuum value of the furnace chamber after evacuation is less than 5×10 -3Pa, then arc melting is carried out under the protection of inert gas argon, the melting process current is 400-600A, the electromagnetic stirring current is 5-10A, the melting time is about 3-4min, after the arc is extinguished and the melting is stopped, the raw material is rapidly solidified into an ingot under the action of circulating cooling water at the bottom of the crucible, and then turned over and melted again, melting for 6 times or more, to obtain a TiZrNbSn alloy ingot with uniform composition;

[0038] Step 2: the TiZrNbSn alloy ingot obtained in step 1 is subjected to a vacuum of less than 5×10 -3 Pa, homogenization heat treatment at 1000℃ for 2h, and then water cooling to room temperature;

[0039] Step 3, cold rolling the TiZrNbSn alloy ingot after the treatment in step 2, wherein the cold rolling process is to perform multiple passes of same-direction rolling at room temperature until the deformation is greater than 90%;

[0040] Step 4: subjecting the alloy plate to a solution heat treatment at 900° C. for 0.5 h under argon protection, and then water-cooling to room temperature to obtain a β-phase TiZrNbSn alloy.

[0041] Example 1

[0042] The TiZrNbSn alloy consists of the following components in atomic percentage: 35% Zr, 9% Nb, 1.5% Sn, and the balance being Ti and inevitable impurities.

[0043] Select raw materials according to the components, put Ti, Zr, Nb and Sn into the crucible of the vacuum argon arc melting furnace according to the proportion, put Ti, Zr and Sn at the bottom of the crucible, put Nb on the surface of the other three raw materials, first draw low vacuum twice to 5Pa and fill the furnace cavity with high-purity argon gas to flush, then draw high vacuum to 5×10 -3 Pa and high-purity argon gas is filled in again as a protective gas, followed by vacuum argon arc melting, the melting current is 400-600A, the current is gradually increased to 600A, melting for 1 minute, then reduced to 500A, melting for 1 minute, and finally reduced to 400A, melting for 1 minute, and then extinguishing the arc; the electromagnetic stirring current during the melting process is 5-10A, when the current reaches 600A, the electromagnetic stirring current is increased to 10A, when the current is 500A, the electromagnetic stirring current is 8A, when the current is 400A, the electromagnetic stirring current is 5A, and when the arc is extinguished, the electromagnetic stirring current is 0A. After the arc is extinguished and the melting is stopped, the raw materials are rapidly solidified into ingots under the action of circulating cooling water at the bottom of the crucible. In order to ensure the uniform composition of the alloy, the ingot is turned over and re-melted, and smelted 7 times to obtain a TiZrNbSn alloy ingot with uniform composition.

[0044] The TiZrNbSn alloy ingot was cast in a vacuum of less than 5×10 -3Pa, homogenization treatment was carried out at 1000℃ for 2h in the β phase region of the alloy, and water-cooled to room temperature. Subsequently, the plate was rolled into a plate in multiple passes in the same direction at room temperature, with an average thickness of 1mm and a rolling deformation of about 92%. Then, the plate was solution treated at 900℃ under argon protection, kept warm for 0.5h, and then water-cooled to room temperature to finally obtain a β phase TiZrNbSn alloy.

[0045] The obtained grain orientation distribution diagram of TiZrNbSn alloy along the rolling direction is shown in Figure 1 As shown in the figure, the alloy is a β single phase structure with an average grain size of 144μm. Most of the grains have <110> Oriented texture, after analysis, such as Figure 2 As shown, <110> The texture accounts for 86.40%. Figure 3 is the cyclic tensile stress-strain curve of TiZrNbSn alloy, the maximum total recovery strain ε r is 4.28%, and the maximum superelastic recovery strain ε se is 3.16%. Figure 4 Its elastic modulus (E) can be calculated to be 41.34 GPa. From the above performance indicators, it can be seen that the TiZrNbSn alloy has the characteristics of ultra-low elastic modulus and high superelasticity.

[0046] The above-mentioned embodiments only express the specific implementation of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be based on the attached claims.

Claims

1. A design method for ultra-low elastic modulus and high superelastic TiZrNbSn alloy, characterized in that: The specific steps include: Step 1, designing the composition of the Zr element. The elastic modulus of the alloy is determined by the bonding force between atoms in the alloy. The weaker the bonding force, the lower the elastic modulus. The atomic bonding force is estimated according to the melting temperature in the Ti-Zr alloy binary phase diagram. When the Zr content is 35 at.%, it corresponds to the lowest melting temperature. At this time, the bonding force between atoms is the lowest and the elastic modulus is the lowest. The Zr content is designed to be 34.5-35.5 at.%; Step 2, designing the composition of the Nb element. According to the critical electron / atom ratio function of the Ti-M alloy, when the valence electron concentration is 4.09, the elastic modulus is the lowest, and a metastable β-titanium structure can be obtained. In the TiZrNbSn alloy, e / a=4+(5-4)*(Nb at.%), and the Nb content is designed to be 8.7-9.3 at.%. Step 3, design the composition of Sn element, and adjust the martensitic transformation end temperature A according to different alloy elements. f The impact of A f [℃] = 1165-75·Nb[at%]-10·Zr[at%]-100·Sn[at%], designing the A of TiZrNbSn alloy f At around room temperature, the Sn content is designed to be 1.4 to 1.6 at.%.

2. An ultra-low elastic modulus and high superelastic TiZrNbSn alloy, comprising Ti, Zr, Nb and Sn elements, characterized in that: The composition of the TiZrNbSn alloy includes 34.5-35.5% Zr, 8.7-9.3% Nb, 1.4-1.6% Sn, and the balance is Ti and inevitable impurities, and the purity of the raw materials is 99.99%.

3. A method for preparing an ultra-low elastic modulus high superelastic TiZrNbSn alloy, characterized in that: The specific steps include: Step 1, Ti, 34.5-35.5% Zr, 8.7-9.3% Nb, and 1.4-1.6% Sn raw materials are loaded into a crucible of a vacuum argon arc melting furnace in proportion, the furnace chamber is evacuated and filled with inert gas as a protective gas, an ingot is obtained after melting once, and then the ingot is turned over and melted multiple times to obtain a TiZrNbSn alloy ingot; Step 2, performing homogenization heat treatment on the TiZrNbSn alloy ingot obtained in step 1, and then water cooling to room temperature; Step 3, cold rolling the TiZrNbSn alloy ingot processed in step 2 to obtain an alloy plate; Step 4: performing a solution heat treatment on the alloy plate obtained in step 3 to obtain a β-phase TiZrNbSn alloy.

4. The method for preparing a superelastic TiZrNbSn alloy with ultra-low elastic modulus according to claim 3, characterized in that: The pressure of the furnace chamber after vacuuming in step 1 is less than 5×10 -3 Pa, smelting is carried out under the protection of inert gas argon, the current of the smelting process is 400-600A, and the electromagnetic stirring current is 5-10A. After stopping the smelting, the raw materials are quickly solidified into ingots under the action of circulating cooling water at the bottom of the crucible, and then the ingots are turned over and re-smelted to obtain TiZrNbSn alloy ingots with uniform composition.

5. The method for preparing a superelastic TiZrNbSn alloy with ultra-low elastic modulus according to claim 4, characterized in that: Smelt 6 times or more in step 1.

6. The method for preparing a superelastic TiZrNbSn alloy with ultra-low elastic modulus according to claim 3, characterized in that: In step 2, the homogenization heat treatment is carried out at a vacuum degree of less than 5×10 -3 Pa, heat treatment at 1000℃ for 2h.

7. The method for preparing a superelastic TiZrNbSn alloy with ultra-low elastic modulus according to claim 3, characterized in that: The cold rolling process in step 3 is a multi-pass rolling in the same direction at room temperature.

8. A method for preparing an ultra-low elastic modulus and high superelastic TiZrNbSn alloy according to any one of claims 3 or 7, characterized in that: The cold rolling deformation in step 3 is greater than 90%.

9. The method for preparing a superelastic TiZrNbSn alloy with ultra-low elastic modulus according to claim 3, characterized in that: In step 4, the solution heat treatment is performed at 900° C. for 0.5 h under argon protection, and then water-cooled to room temperature.

Citation Information

Patent Citations

  • Beta type Zr-Ti-Nb-Sn system alloy and preparation method thereof

    CN105274393A

  • Low-elasticity-modulus high-fatigue-strength biologic implantable titanium alloy and preparation method thereof

    CN105420549A

  • Super-elasticity low-elastic-modulus titanium alloy material and preparation method and application thereof

    CN105714149A

  • Titanium alloy with low elastic modulus and high superelasticity and preparation method thereof

    CN116790938A

  • Hyperelastic low-modulus TiZrNbSn alloy and preparation method thereof

    CN118028658A